Pengaruh Kualitas Produk, Saluran Distribusi Dan Harga Terhadap Keputusan Pembelian (Studi Kasus pada Konsumen Bandung Super Model Jalan Raya Sengkaling Malang) - Ridha Luthfi Setiawan; N. Rachma; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract                                              The development of free markets in the world has made entrepreneurs to always update every product they produce. Starting from the quality, distribution to the price of the product. This study aims to determine the effect of product quality, distribution channels, and price on consumer purchasing decisions in Bandung Super Model Malang simultaneously and partially, and look for dominant variables. The type of research used is explanatory research. This research was conducted on Consumers Bandung Super Model Jalan Raya Sengkaling Malang. The time of the research was carried out in October 2020 - January 2021. The population in this study was the consumers of the Bandung Super Model Malang with a total of 500 people. While the sample size in this study was 96 respondents. Based on the results of the study, it is known that the variables of product quality, distribution channels, and marketing strategies simultaneously influence purchasing decisions. Partially or individually the variables of product quality, distribution channels, and price affect consumer purchasing decisions in Bandung Super Model Malang. Keywords: Product Quality, Distribution Channels, price, Purchase Decision